INNOVATION MANAGEMET CLASS PADA MATA PELAJARAN FIQIH DI MADRASAH IBTIDAIYAH MIFTAHUL HUDA 1 PALANGKA RAYA - Syahmidi; Nor Aida; Surawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Classroom management is one of the important skills that must be mastered by teachers, because it can support success in the learning process. This study aims to explore the application of classroom management innovation in Fiqh learning at Madrasah Ibtidaiyah Miftahul Huda 1 Palangka Raya. The method used is qualitative with a phenomenological approach. Data collection techniques were carried out through observation, interviews and documentation, and data validation techniques using source triangulation. The results showed that classroom management innovation was carried out through four main aspects, namely understanding the situation and conditions of students, applying varied learning methods, using learning media, and structuring the learning environment. Teachers adjust learning strategies to student conditions, apply interactive methods such as discussion and question and answer with rewards, and utilize visual media and teaching aids. In addition, seating arrangements are made to improve student comfort and interaction. This research shows that innovative strategies in classroom management can create a conducive learning atmosphere and improve student engagement and understanding.